An Review On Entrepreneurship Development Cell - Doshi, Saurabh; Mohan, Paresh; Singh, Roshan; Singh, Sandeep; Kabra, Mahaveer Prasad (Asian Journal of Pharmaceutical Research and Development, 2018)
In India, a large number of Science & Technology institutions as well as institutions of higher learning have emerged since Independence as a result of systematic and conscious initiatives of the Government. Many of these are comparable to the best institutions in the world. These institutions are churning out large number of trained manpower, thus fulfilling the need of the industry, R&D institutions and other sectors of economy. Entrepreneurship can be defined by describing what entrepreneurs do. For example: "Entrepreneurs use personal initiative, and engage in calculated risk-taking, to create new business ventures by raising resources to apply innovative new ideas that solve problems, meet challenges, or satisfy the needs of a clearly defined market." Entrepreneur is a person who organises/ manages the risks in his/her enterprise. “Entrepreneur is a individual who takes risks and starts something new”. Entrepreneurship plays an important role in the economic growth and development of nation. It is a purposeful activity includes in initiation, promotion and distribution of wealth and service. India has been one of the fastest growing economies of the past decade. Indian economic growth has been characterized by multifaceted development – increases in production have been consistent and robust, and the economy has displayed clear indicators of shifting from an agrarian one to one in which services like business services, banking, communications, etc. play a major part.